O Carvedilol Protege Mitocôndrias Cardíacas Isquémicas de Lesões Induzidas Por Stress Oxidativo - Carreira, R (2004)
Ischemia negatively affects mitochondrial function by inducing the mitochondrial permeability transition (MPT). The MPT is triggered by oxidative stress, which occurs in mitochondria during ischemia as a result of diminished antioxidant defenses and increased reactive oxygen species production. It causes mitochondrial dysfunction and can ultimately lead to cell death. Therefore, drugs able to minimize mitochondrial damage induced by ischemia may prove to be clinically effective. We analyzed the effect of carvedilol, a beta-blocker with antioxidant properties, on mitochondrial dysfunction. Carvedilol decreased levels of TBARS (thiobarbituric acid reactive substances), an indicator of oxidative stress, which is consistent with its antioxidant properties. Regarding cell death by apoptosis, although ischemia did increase caspase-8-like activity, there were no changes in caspase-3-like activity, which is activated downstream of caspase-8; this may indicate that the apoptotic cascade is not activated by 60 minutes of ischemia. We conclude that carvedilol protects ischemic mitochondria by preventing oxidative mitochondrial damage, and, by so doing, it may also inhibit the formation of the MPT pore.